2021
DOI: 10.3390/cancers14010197
|View full text |Cite
|
Sign up to set email alerts
|

Combined Fluorescence and Optoacoustic Imaging for Monitoring Treatments against CT26 Tumors with Photoactivatable Liposomes

Abstract: The newly developed multimodal imaging system combining raster-scan optoacoustic (OA) microscopy and fluorescence (FL) wide-field imaging was used for characterizing the tumor vascular structure with 38/50 μm axial/transverse resolution and assessment of photosensitizer fluorescence kinetics during treatment with novel theranostic agents. A multifunctional photoactivatable multi-inhibitor liposomal (PMILs) nano platform was engineered here, containing a clinically approved photosensitizer, Benzoporphyrin deriv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 95 publications
0
6
0
Order By: Relevance
“…In this paper, age-related changes in the vascular bed of the skin of healthy volunteers are assessed in vivo for the first time using the OA angiographic technique. As a criterion for analyzing age-related changes in the skin, various parameters of the vascular network of the skin were calculated using a recently developed [25] and successfully applied in [26] algorithm for processing the three-dimensional OA images based on graph representation of the vascular net. The proposed algorithm was used to calculate the parameters characterizing the average density of the vessels, the length of the vessels, and the branching of the vessels on the basis of a graph constructed from a skeletonized image.…”
Section: Introductionmentioning
confidence: 99%
“…In this paper, age-related changes in the vascular bed of the skin of healthy volunteers are assessed in vivo for the first time using the OA angiographic technique. As a criterion for analyzing age-related changes in the skin, various parameters of the vascular network of the skin were calculated using a recently developed [25] and successfully applied in [26] algorithm for processing the three-dimensional OA images based on graph representation of the vascular net. The proposed algorithm was used to calculate the parameters characterizing the average density of the vessels, the length of the vessels, and the branching of the vessels on the basis of a graph constructed from a skeletonized image.…”
Section: Introductionmentioning
confidence: 99%
“…In a similar approach, Turchin’s group proposed a liposomal photoactivatable multifunctional nanoplatform (PMIL) carrying a lipid-anchored derivative of BPD in the bilayer and IRI in an inner aqueous core [ 112 ]. In vivo studies on BALB/c mice injected with colon carcinoma CT26 cells demonstrated higher therapeutic efficacy (97% inhibition of tumor growth) following treatment with PMIL compared to BPD containing liposomes (81% inhibition) or IRI containing liposomes (50%).…”
Section: Drug Delivery Systems For Pss and Chemotherapeutics: An Over...mentioning
confidence: 99%
“…34 To maximize the therapeutic potential of PDT-based combination therapies several nanoformulations with PSs and chemotherapeutics have been reported. 34,59,91,160,161 Liang et al reported a nanoliposomal formulation combining Verteporfin and irinotecan where Verteporfin conjugated anti-EGFR antibodies (Photoimmunoconjugates; PIC) were further conjugated to irinotecan loaded liposomes generating the formulation PIC-Nanoliposomes (PIC-NL) (Figure 12A). 133 The efficacy of the construct was found to be EGFR specific and showed 20% more cytotoxicity as compared to the combination of PIC + Nal − IRI.…”
Section: Photosensitizer-loaded Liposomesmentioning
confidence: 99%